An overview of sustainable business models for innovation in Swedish agri-food production - Per-ola Ulvenblad; Pia Ulvenblad; Joakim Tell (Journal of Integrative Environmental Sciences, 2019)
Companies in the agri-food sector are under increasing pressure to adopt sustainable business models that consider not only economic but also both social and environmental aspects. This paper examines how Swedish food producers use sustainable business models to innovate their businesses. The empirical data comes from a telephone survey with 204 companies and from case studies of 4 companies. A conceptual framework regarding sustainability-oriented innovation (SOI) and a eight sustainable business model archetypes are used to map and analyse the sustainability innovation practices and the sustainable business models. The results show a surprisingly sustainable business focus taken by many companies, which is not only on optimization, but also on organizational transformation and on systems building. The results show the companies vary as far as which archetypes they match. The most common archetype matches are ‘Maximise material and energy efficiency’ and ‘Adopt a stewardship role’. Only 10% measure success solely in financial terms, while 80% measure success in financial terms as well as social and environmental terms. Another conclusion is that companies in the agri-food sector have unique characteristics and the value intention of the entrepreneurs is an important building block in sustainable business model innovation.